An exploratory study of organisational culture and employee commitment: a case study at a local municipality - Adams, Joy-Ann Rachelle; Van Rooyen, Joy-Ann Rachelle (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.